Policy Implication of the Awareness and Use of Biotechnology Products Among Farmers in Aboh-Mbaise Local Government Area of Imo State, Nigeria - E C Matthews-Njoku; O M Adesope (Journal of Agricultural Extension, 2014)
The study investigated awareness of and extent of the use of biotechnology products among farmers in Aboh-Mbaise local government area of Imo State, Nigeria. Data for the study were collected with the aid of structured questionnaire from 60 randomly selected respondents in the study area. Data were analyzed using frequencies, percentages and mean scores. The study revealed that majority (88.3 percent) of the respondents are aware of the existence of biotechnology products and majority (76.7 percent) of the respondents use biotechnology products. It was observed that genetically modified cassava variety is the most used biotech product in the study area as it scored a mean of 3.25 followed by biotech maize and tree crops which scored means of 2.68 and 2.67 respectively. It was also revealed that genetically modified cassava varieties was the most available biotech product in the study area, and closely followed by biotech tree crops. In the same vein biotech cassava variety is the most used biotech product in the study area. Based on the findings of this study, the following recommendations are made: There is need for adequate and proper education of farmers about biotechnology and its relative advantages. Adequate extension policy on availability of genetically modified yam, cowpeas, sorghum, millet and vegetables will meet help to meet the needs of the farmers and other end users. It is only if they are available that they can be utilized.Â